2022
DOI: 10.1038/s41598-022-16679-1
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of etomidate combined with dexmedetomidine on adrenocortical function in elderly patients: a double-blind randomized controlled trial

Abstract: Etomidate has been advocated to be used in anesthesia for the elderly and the critically ill patients due to its faint effect on cardiovascular system. But the dose-dependent suppression of etomidate on adrenal cortex function leads to the limitation of its clinical application. Clinical research showed that dexmedetomidine could reduce the dose requirements for intravenous or inhalation anesthetics and opioids, and the hemodynamics was more stable during the operation. The objective was to observe the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A significant association of etomidate with adrenal insufficiency has been established. Etomidate specifically and reversibly blocks 11α-hydroxylation and 11β-hydroxylation in adrenal steroid synthesis, leading to decreases in the synthesis of cortisol, corticosterone, and aldosterone ( 6 ) ( Figure 3 ). Cortisol is the most abundant endogenous glucocorticoid ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…A significant association of etomidate with adrenal insufficiency has been established. Etomidate specifically and reversibly blocks 11α-hydroxylation and 11β-hydroxylation in adrenal steroid synthesis, leading to decreases in the synthesis of cortisol, corticosterone, and aldosterone ( 6 ) ( Figure 3 ). Cortisol is the most abundant endogenous glucocorticoid ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that dexmedetomidine has neuroprotective and anti-inflammatory properties and improves postoperative cognitive dysfunction in older patients [ 5 7 ]. In previous clinical study, we found that the combination of dexmedetomidine and etomidate could maintain perioperative hemodynamic stability and reduce the inhibitory effect of etomidate on adrenocortical function in older patients [ 8 ]. However, there is no report on the effect of the combination of etomidate and dexmedetomidine for anaesthesia on postoperative cognitive function of older patients, and it is not clear whether the combination of etomidate and dexmedetomidine with different anaesthesia time has different effects on postoperative cognitive function of older patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous reports, the use of propofol has an increased risk ratio for hypotension compared with the use of etomidate during endoscopy [23,24] . However, etomidate is limited by myoclonus and postoperative nausea and vomiting (PONV), and there are also concerns regarding its cortisol suppressive function [25] . Therefore, etomidate is considered a twoedged sword when used for induction [26] .…”
Section: Introductionmentioning
confidence: 99%